2007
DOI: 10.1007/s00705-006-0931-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gene constellation and postreassortment amino acid change on the phenotypic features of H5 influenza virus reassortants

Abstract: Reassortants between a low-pathogenic avian influenza virus strain A/Duck/Primorie/2621/2001 (H5N2) and a high-yield human influenza virus strain A/Puerto Rico/8/34 (H1N1) were generated, genotyped and analyzed with respect to their yield in embryonated chicken eggs, pathogenicity for mice, and immunogenicity. A reassortant having HA and NA genes from A/Duck/Primorie/2621/2001 virus and 6 genes from A/Puerto Rico/8/34 virus (6:2 reassortant) replicated efficiently in embryonated chicken eggs, the yields being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Thus, the reassortants, which contain the HA and NA genes of a human epidemic virus and the other genes of PR8 virus were shown to be as high-yield as the parent PR8 strain (6). Conversely, the reassortants having HA and NA of avian influenza viruses often produce moderate yields in the embryonated chicken eggs, intermediate between the yield of the avian parent virus and the A/Puerto Rico/8/34 (H1N1) strain (8,14). In the present studies we detected a similar situation with respect to the pandemic "swine-like" virus of 2009.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Thus, the reassortants, which contain the HA and NA genes of a human epidemic virus and the other genes of PR8 virus were shown to be as high-yield as the parent PR8 strain (6). Conversely, the reassortants having HA and NA of avian influenza viruses often produce moderate yields in the embryonated chicken eggs, intermediate between the yield of the avian parent virus and the A/Puerto Rico/8/34 (H1N1) strain (8,14). In the present studies we detected a similar situation with respect to the pandemic "swine-like" virus of 2009.…”
supporting
confidence: 68%
“…In our previous studies with avian-human reassortants we observed an expressed increase of virus yield produced by the introduction of the avian virus PB1 gene in the genetic content of the reassortant (14). An enhancement of virus yield by the introduction of the PB1 gene of the 2009 pandemic virus in the genetic content of a reverse genetics-derived reassortant was also reported (16).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Recently, Rudneva et al reported that the introduction of the PB1 gene from a low pathogenic avian virus of the H5N2 subtype increased the replication of a corresponding 5 + 2 + 1 PR8 reassortant compared to the conventional 6 + 2 reassortant [37]. Moreover, two reassorted PR8-based vaccine seeds carrying the surface glycoprotein genes of the seasonal Pan99 (H3N2) virus had also received the PB1 gene of the epidemic strain [26].…”
Section: Discussionmentioning
confidence: 99%
“…PB1 from a seasonal strain or with targeted mutations has been shown to improve growth or HA yield of H3 reassortants (Cobbin et al, 2013;Plant et al, 2012); however, mixed results have been observed for H5 reassortants (Abt et al, 2011;Rudneva et al, 2007;Wanitchang et al, 2010). All three polymerase segments reassort together more frequently in experimental settings than natural reassortment, suggesting gene constellation effects (Macken et al, 2006;Varich et al, 2008;Wille et al, 2013).…”
mentioning
confidence: 99%